Best–worst method to prioritize indicators effective in making logistics systems more sustainable in fast-moving consumer goods industry in developing countries - Pishdar, Mahsa; Ghasemzadeh, Fatemeh; Antuchevičienė, Jurgita (Transport, 2022)
Logistics systems constitute the backbone of international trade. For developing countries, establishment of sustainable logistics systems reduces costs, and makes supply chains strong to become able to compete. Without setting indicators for sustainable logistics, it is not possible to understand what policies are necessary for success. Logistics systems situations become worse in especial industries such as Fast-Moving Consuming Goods (FMCG) industry that are facing observable challenges such as old-fashioned goods or product corruption. The objective of this paper is to determine a set of indicators, which can be helpful in enhancement of sustainable logistics systems in developing countries. An initial set of indicators is determined through literature review and justified by asking experts’ opinions who have experience of management in logistics systems in developing countries such as Iran and Afghanistan, especially in logistics management in FMCG industry. The indicators are prioritized using Best–Worst Method (BWM), which is a newly introduced decision-making model. Results of prioritization of finalized dimensions and indicators by use of BWM show that “Governance” has the highest importance among dimensions and “management commitment to sustainability” is the most important indicator among all indicators. The results are applicably acceptable as we can see in business circumstances that only when managers believe in perusing sustainability principles as an important factor under each type of economic circumstance, an efficient vision will be set. Risk management has gained the least weight in this study. Based on experts’ opinions, if policies and procedures are set and performed correctly, risks will be less probable by themselves. The results help mangers in assignment of limited budgets to improvement projects related to each indicator.